A CRITICAL REVIEW ON ACTION OF SWEDANA VIS-A-VIS SUDATION THERAPY - Akhilanath Parida; Satyasmita Jena; Varun Sawant (International Journal of Ayurveda and Pharma Research, 2020)
Swedanam is a therapy which alleviates stiffness, heaviness, coldness & that which brings out sweating from the system is sudation therapy. The perspiration brought about by the sudation therapy is more than the normal. Conventionally the sudation therapy is just understood as the steam bath, but sudation in Ayurveda is something more as a treatment & as a daily routine. Swedana drugs by Ushna and Tikshnaguna are capable of penetrating the microcirculatory channels (Srotas) where they activate the sweat glands to produce mores heat. Swedana Karma hastens this process by increasing the permeability of capillary and bringing the morbidities into an extracellular fluid by dilating and clearing the channels of the body. Swedanakarma maintains the thermoregulation system of the body by maintaining quilibrium between core temperature (temp. inside the body) and shell temperature (skin temp).